1999
DOI: 10.1017/s0950268899002873
|View full text |Cite
|
Sign up to set email alerts
|

Microbial quality of oysters sold in Western Trinidad and potential health risk to consumers

Abstract: The prevalence and characteristics of Escherichia coli and Salmonella spp. as well as counts of E. coli in raw oysters, condiments/spices, and raw oyster cocktails sampled from 72 vendors across Western Trinidad were determined. The microbial quality of the water used in the preparation of raw oysters was also investigated. Of 200 samples each of raw oysters, condiments/spices and oyster cocktails tested, 154 (77.0%), 89 (44.5%) and 154 (77.0%) respectively yielded E. coli. The differences were statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Although the intent was not to draw quantitative comparisons between the prevalence of contamination of domestic and imported produce, the different detection rates might reflect differences in conditions during pre-and post-harvest operations. Based on the studies included in the present review (Table 2), Salmonella-contaminated spices and herbs were also detected in surveys from Brazil (Moreira, Lourenção, Pinto, & Rall 2009), Japan (Hara-Kudo et al, 2006), India (Banerjee & Sarkar 2003), Trinidad (Rampersad et al, 1999), and Austria (Kneifel & Berger 1994). In the study of Moreira et al (2009) examining the microbial status of various commodities (basil, bay leaves, black pepper, cinnamon, clove, cumin, dehydrated green onion, dehydrated parsley, oregano) marketed in São Paulo, 13 (5.6%) of 233 samples were positive for Salmonella.…”
Section: Salmonella-related Outbreaks Caused By Spices and Herbsmentioning
confidence: 78%
“…Although the intent was not to draw quantitative comparisons between the prevalence of contamination of domestic and imported produce, the different detection rates might reflect differences in conditions during pre-and post-harvest operations. Based on the studies included in the present review (Table 2), Salmonella-contaminated spices and herbs were also detected in surveys from Brazil (Moreira, Lourenção, Pinto, & Rall 2009), Japan (Hara-Kudo et al, 2006), India (Banerjee & Sarkar 2003), Trinidad (Rampersad et al, 1999), and Austria (Kneifel & Berger 1994). In the study of Moreira et al (2009) examining the microbial status of various commodities (basil, bay leaves, black pepper, cinnamon, clove, cumin, dehydrated green onion, dehydrated parsley, oregano) marketed in São Paulo, 13 (5.6%) of 233 samples were positive for Salmonella.…”
Section: Salmonella-related Outbreaks Caused By Spices and Herbsmentioning
confidence: 78%
“…Studies done to find out the bacteriological quality of the water used by some street vendors have revealed frequent contamination with coliforms and fecal coliforms [43]. When the street foods in Trinidad and Tobago were analyzed, it was reported found that 35% of foods were contaminated by E. coli while 57.5% of water used by vendors were contaminated by coliforms [26,[44][45][46]. These reports were similar to the findings that the stored water used by consumers and vendors, at the vending site, showed heavy bacteriological contamination of faecal origin [31].…”
Section: Watermentioning
confidence: 99%
“…E. coli O157 has also been isolated from the water supply to rural communities (2.0%) (Welch et al 2000) [13], local delicacies such as oysters (2%) (Rampersad et al 1999) [14] and 'black pudding' (13.6%) (Adesiyun and Balbirsingh 1996 [9]) and from pre-processed cows' milk (0.8%) (Adesiyun et al 2007) [12]. The first case of neonatal septicaemia and meningitis due to L. monocytogenes was reported in Trinidad in 1998, (Ashiru and Bratt 1998) [15] when symptoms appeared three days after a blood transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…In Trinidad and Tobago, Salmonella spp. have been recovered from oysters, 2.3% (Rampersad et al 1999) [14], black pudding, 8% (Adesiyun and Balbirsingh 1996) [9] and table eggs, 13.0% (Adesiyun et al 2005) [16].…”
Section: Introductionmentioning
confidence: 99%